Surface Acoustic Wave Devices Computer Models: Application and Perspectives - Budrevičius, R.; Rupkus, S. (Elektronika ir Elektrotechnika, 2004)
Surface acoustic wave (SAW) devices are very modern. In this paper are studied physical SAW device operation parameters. They allow to make statistic analysis of results. There is provided the method of acceptance of modeling by components for SAW devices, as well as generating expressions and presented generalizing formulas. Also there is analyzed the SAW design program. SAW characterization mathematical equation are presented. Experimental and theoretical results are presented. Ill. 4, bibl. 6 (in Lithuanian; summaries in Lithuanian, English and Russian).